Internalisasi Nilai-Nilai Akhlak Islami melalui Pemanfaatan Media Sosial Peserta Didik MAS Plus Al-Ulum - Ramadhani, Jalwa Suci (YPI Ulul Albab, 2025)
The development of information technology in the digital era has had a significant impact on the education and moral development of the younger generation, particularly students at MAS Plus Al-Ulum. Social media has become an important tool not only for communication but also for seeking information, expressing oneself, and shaping daily thought patterns and behaviors. This study aims to describe the process of internalizing Islamic moral values ​​through students' use of social media. The methods used include observation, interviews, and documentation studies. The results show that social media can support moral learning when used wisely, such as by following educational accounts, engaging in polite discussions, and creating positive content. Teachers play a strategic role in guiding students so that their digital experiences reinforce Islamic values, including honesty, responsibility, caring, and social ethics. However, inappropriate use of social media can have negative impacts, such as the spread of unverified information. Therefore, the role of teachers and parents is crucial in guiding and supervising students' interactions in the digital world to ensure optimal moral internalization.